DIET AND AWARENESS OF STUDENTS ABOUT HEALTHY EATING - A. Andonova (Trakia Journal of Sciences)
An important factor influencing human health is food. The improvement of healthy nutrition is one of the leading principles for improving the health of the population. Forming habits for healthy nutrition in children should be realized as a shared responsibility between family, school and society. MATERIALS AND METHODS: An anonymous study was conducted with 100 students aged between 14 and 18 years old, elected at random principle, with the informed consent of their parents. PURPOSE: The purpose of the study is to know the level of awareness of students about the principles of healthy nutrition and their observance. RESULTS: The study found out that 46% of students know the principles of healthy nutrition, and 26% - partially. Information about healthy nutrition 83% of students receive from family, 48% - from school, 45% - from the Internet, 41% - from television, 38% - from friends. According to their selfassessment, 46% of the respondents know the principles of healthy nutrition, 30% follow them, and 49% strive to follow a healthy diet. According to 40% of students, the principles of healthy nutrition are followed by their families. 16% have lunch in the school canteen every day, 26% bring healthy food from home every day, and 63% do not have breakfast. According to 60% of the respondents, the healthiest foods are fruit and vegetables. According to 68% of students, the most purchased foods outside school canteens are: burger sandwiches, gyros, bakeries, snacks, and beverages: carbonated drinks of world brands, energy drinks, and fruit juices without interest in the content of sugar and preservatives.